Tratamento por sistemas microemulsionados da borra gerada na flotação de água oleosa de petróleo - Silva, Dennys Correia da (2018)
With the development and expansion of the oil industry, waste generation on a large scale also grows. Environmental contamination by oil and its products stands out as a problem of high impact and requires special care during production and waste treatment. In the effluent treatment stage aiming the removal of oil from water by flotation, a sludge is generated which presents itself as a great challenge of treatment for either disposal or a possible reuse viability. This work presents a treatment option for the flotation sludge (FS) through microemulsion systems involving saponified coconut oil (SCO) and the commercial demulsifier Dissolvan as surfactants. The flotation slurry (BF) was extracted in soxhlet and provided the following fractions: 87.64% oil, 8.09% water and 4.26% insoluble residues. These insoluble residues of the sludge, and the residue of the flocculating agent used in the flotation of the oil, went through stages of identification and characterization through X-ray Diffraction (XRD), X-ray Fluorescence Spectrometry (XRF), Infrared Spectroscopy (FT-IR), Thermogravimetric Analysis (TGA), Scanning Electron Microscopy (SEM), Energy Dispersive Spectroscopy (EDS), Elemental Analysis (CHNO) and UV-Vis Absorption Spectroscopy. The presence of quartz (SiO2), calcite (CaCO3), pyrite (FeS2) and molybdenite (MoS2) was observed in the flotation sludge residue, while FRX confirmed the presence of these minerals by sulfur (35.48%), iron (28.16%) and residual cation fractions. Chlorine (56.12%), aluminum (17.71%), sulfur (6.93%) and cation residues were detected in the flocculating agent residue. These characterizations revealed the presence of minerals from the geological formations, corresponding to 20% of the mass of the sludge residue as indicated by the thermogravimetric analysis, while the analyzes of FT-IR, SEM and EDS showed similarities between the residues of the two samples. Moreover, the CHNO and UV-Vis Absorption Spectroscopy analyzes identified the flocculant agent residue as a condensed tannin because of the number of components and similarities between the absorption spectrum of a sample of condensed tannin extracted from the Ipomea pes-caprae plant. In addition, an optimization process for solubilization of FS was evaluated using a microemulsion system (MES) containing SCO as surfactant, n-butanol as cosurfactant, aviation fuel as the oil phase and NaCl 2% salt water as the aqueous phase solution. Winsor systems were obtained, and microemulsion phases were characterized at room temperature (25°C) by analyzing visual appearance, particle size, zeta potential, surface tension, pH, electrical conductivity and small angle X-ray scattering (SAXS). The optimization of the use of microemulsion phases of WII and WIV systems in the sludge solubilization was evaluated through a central composite rotatable design (CCRD) at two application points: Winsor II rich in water and Winsor IV rich in oil. The microemulsion phases of these points were applied in order to investigate and estimate possible factors that may increase the solubility efficiency of the sludge, having as variables MES/FS ratio, temperature (°C) and time (min). From the data obtained for the two points, it was verified that the values acquired for the solubilization efficiency (ES) were, in almost all the tests, greater than 90%, excepting the tests in which the solubilization time and the MES/FS ratio were very low, and thus efficiency values ranged from 70-80%. The microemulsion system containing Dissolvan as surfactant revealed to have higher solubilization capacity (93.36% for WII rich in salt water and 95.79% for WII rich in oil phase) compared to the SCO system (91.89% for WII and 95.6% for WIV), which validates its use in the treatment of microemulsion flotation sludge.